A new method to improve running economy and maximal aerobic power in athletes: Endurance training with periodic carbon monoxide inhalation - Wang, J.; Ji, Y.; Zhou, L.; Xiang, Y.; Heinonen, I. H.; Zhang, P. (Frontiers in Physiology, 2019)
Background: Altitude training stimulates erythropoietin hormone (EPO) release and increases blood hemoglobin (Hb) mass, which may result in improved oxygen (O2) transport capacity. It was hypothesized in the present study that periodic inhalation of carbon monoxide (CO) might elicit similar physiological adaptations compared to altitude training. Methods: Twelve male college student athletes, who were well-trained soccer players, participated. They performed a four-week treadmill-training program, 5 times a week. Participants were randomly assigned into an experimental group with inhaling CO (INCO) (1 mL/kg body weight for 2 minutes) in O2 (4 L) before all training sessions and a control group without inhaling CO (NOCO). CO and EPO concentrations in venous blood were first measured acutely at the 1st, 2nd, 4th, 6th, and 8th hour after INCO, and total hemoglobin mass (tHb), running economy and VO2max were measured before and after the four weeks training intervention. Results: HbCO% increased from 0.7 to 4.4% (P<0.05) after 1 h of CO inhalation and EPO increased from 1.9 to 2.7 mIU/mL after 4 h post CO inhalation (P<0.05) acutely before the intervention. After the training, the tHb and VO2max in the INCO group increased significantly by 3.7 and 2.7%, respectively, while no significant differences were observed in the NOCO condition. O2 uptake at given submaximal speeds declined by approximately 4% in the INCO group. Conclusion: Acutely, EPO increased sharply post CO inhalation, peaking at 4 h post inhalation. 4-weeks of training with CO inhalation before exercise sessions improved tHb and VO2max as well as running economy, suggesting that moderate CO inhalation could be a new method to improve the endurance performance in athletes.